Atitudes democráticas e evangélicos no Brasil: conservadorismo ou antidemocratismo? - Coelho, Victor Alberto Bueno (Universidade Federal de São Carlos, 2025)
The 2018 and 2022 Brazilian presidential elections were marked by the significant support of the evangelical electorate for right-wing candidate Jair Bolsonaro. Journalists, political commentators, and researchers have attempted to explain this support based on the alignment between the conservative values of Brazilian evangelical leaders and those of Jair Bolsonaro. However, few studies have analyzed this phenomenon at the public opinion level, beyond the alignment between a candidate and the leaders of a specific segment of society. Are evangelicals indeed more conservative and authoritarian? This research aims to answer this question and, using data from the Brazilian Electoral Study, identify whether there is a distinct political behavior among Brazilian evangelicals. Preliminary results confirm the need for a closer examination of this group, as they are found to be more conservative than Catholics, adherents of other religions, and atheists, but not necessarily more authoritarian.
Democratic attitudes and evangelicals in Brazil: conservatism or antidemocratism?
Attitudes démocratiques et évangéliques au Brésil : conservatisme ou antidémocratie ?
Keywords: Conservadorismo; Autoritarismo; Evangélicos; Democracia; Conservatism; Authoritarianism; Evangelicals; Democracy; CIENCIAS HUMANAS::CIENCIA POLITICA::COMPORTAMENTO POLITICO